Analisis Kinerja Sistem Drainase Berkelanjutan di Kabupaten Nganjuk - Nazwa Laily Azzahrah; Agil Fitri Handayani; Laras Alencia Eka Putri; Jelita Bulanisahadi; Tee Tze Kiong (Program Studi Arsitektur Universitas Tanri Abeng, 2026)
Urban drainage systems play a crucial role in controlling stormwater runoff and reducing the risk of flooding in urban areas. Nganjuk Regency, as a rapidly developing region, faces challenges in establishing an effective and sustainable drainage management system. This study aims to analyze the performance of the existing drainage system and ensure the implementation of the sustainable drainage concept. The method used is descriptive, with field observation and literature review approaches. The results indicate that drainage performance is still suboptimal due to sedimentation, garbage blockage, and limited air absorption infrastructure. The application of the Sustainable Drainage System (SuDS) concept, such as infiltration wells and bioretention, is still minimal. Therefore, integrated, environmentally-based drainage management is needed to improve system effectiveness and reduce the potential for flooding.